IB History : route 2 : communism in crisis 1976-89 - Gauci, Joe.; OSC Publishing (Oxford : OSC, 2009)
This guide provides a set of detailed and very clear notes organised around the topic areas included in the IBDP syllabus. The bullet-points in the IBDP syllabus have been used as the main heading in this book, on topics such as China under Deng Xiaoping, the aims and policies of Gorbachev, and the revolutions of 1989 in Poland, Czechoslovakia and East Germany. Following the notes, 2 sets of practice source questions are included; 1 set with suggestions for answers, a second without answers for students to have a go at. Advice on improving technique in answering the different types of source-based questions is given.
Standard & higher level.
English.
Keywords: Communism history -- China -- 1976-1989.; Communism -- China -- History; IB Programme -- History; History -- IB Programme